Assessing the Major Aspects and Implications of Telerehabilitation Services: A Bibliometric Analysis - Osama Khalil Alyacoubi; Maria Ulfa; Arlina Dewi (Universitas Muhammadiyah Yogyakarta, 2023)
Telerehabilitation has emerged as a promising option for delivering rehabilitation services to individuals with physical impairments, but its effectiveness, efficiency, and economic implications are not yet fully understood. This study explores the relationship between telerehabilitation services and various aspects of healthcare delivery, including treatment, quality, outcome, and delivery of telerehabilitation. The Scopus database (https://www.scopus.com) with the term